let R be Ring; :: thesis: for V being LeftMod of R
for v1, v2 being Vector of V st R = INT.Ring & V is Mult-cancelable holds
( ( v1 <> v2 & {v1,v2} is linearly-independent ) iff for a, b being Element of R st (a * v1) + (b * v2) = 0. V holds
( a = 0. R & b = 0. R ) )

let V be LeftMod of R; :: thesis: for v1, v2 being Vector of V st R = INT.Ring & V is Mult-cancelable holds
( ( v1 <> v2 & {v1,v2} is linearly-independent ) iff for a, b being Element of R st (a * v1) + (b * v2) = 0. V holds
( a = 0. R & b = 0. R ) )

let v1, v2 be Vector of V; :: thesis: ( R = INT.Ring & V is Mult-cancelable implies ( ( v1 <> v2 & {v1,v2} is linearly-independent ) iff for a, b being Element of R st (a * v1) + (b * v2) = 0. V holds
( a = 0. R & b = 0. R ) ) )

assume A1: ( R = INT.Ring & V is Mult-cancelable ) ; :: thesis: ( ( v1 <> v2 & {v1,v2} is linearly-independent ) iff for a, b being Element of R st (a * v1) + (b * v2) = 0. V holds
( a = 0. R & b = 0. R ) )

thus ( v1 <> v2 & {v1,v2} is linearly-independent implies for a, b being Element of R st (a * v1) + (b * v2) = 0. V holds
( a = 0. R & b = 0. R ) ) :: thesis: ( ( for a, b being Element of R st (a * v1) + (b * v2) = 0. V holds
( a = 0. R & b = 0. R ) ) implies ( v1 <> v2 & {v1,v2} is linearly-independent ) )
proof
assume A2: ( v1 <> v2 & {v1,v2} is linearly-independent ) ; :: thesis: for a, b being Element of R st (a * v1) + (b * v2) = 0. V holds
( a = 0. R & b = 0. R )

let a, b be Element of R; :: thesis: ( (a * v1) + (b * v2) = 0. V implies ( a = 0. R & b = 0. R ) )
assume that
A3: (a * v1) + (b * v2) = 0. V and
A4: ( a <> 0. R or b <> 0. R ) ; :: thesis: contradiction
now :: thesis: contradiction
per cases ( a <> 0. R or b <> 0. R ) by A4;
suppose A5: a <> 0. R ; :: thesis: contradiction
a * v1 = - (b * v2) by
.= (- (1. R)) * (b * v2) by ZMODUL01:2
.= ((- (1. R)) * b) * v2 by VECTSP_1:def 16 ;
hence contradiction by A1, A2, A5, Th62; :: thesis: verum
end;
suppose A6: b <> 0. R ; :: thesis: contradiction
b * v2 = - (a * v1) by
.= (- (1. R)) * (a * v1) by ZMODUL01:2
.= ((- (1. R)) * a) * v1 by VECTSP_1:def 16 ;
hence contradiction by A1, A2, A6, Th62; :: thesis: verum
end;
end;
end;
hence contradiction ; :: thesis: verum
end;
assume A7: for a, b being Element of R st (a * v1) + (b * v2) = 0. V holds
( a = 0. R & b = 0. R ) ; :: thesis: ( v1 <> v2 & {v1,v2} is linearly-independent )
A8: now :: thesis: for a, b being Element of R st b <> 0. R holds
not b * v1 = a * v2
let a, b be Element of R; :: thesis: ( b <> 0. R implies not b * v1 = a * v2 )
assume A9: b <> 0. R ; :: thesis: not b * v1 = a * v2
assume b * v1 = a * v2 ; :: thesis: contradiction
then b * v1 = (0. V) + (a * v2) by RLVECT_1:4;
then 0. V = (b * v1) - (a * v2) by RLSUB_2:61
.= (b * v1) + (a * (- v2)) by
.= (b * v1) + ((- a) * v2) by ;
hence contradiction by A9, A7; :: thesis: verum
end;
now :: thesis: not v2 = 0. V
assume A10: v2 = 0. V ; :: thesis: contradiction
0. V = (0. V) + (0. V) by RLVECT_1:4
.= ((0. R) * v1) + (0. V) by
.= ((0. R) * v1) + ((1. R) * v2) by ;
hence contradiction by A7, A1; :: thesis: verum
end;
hence ( v1 <> v2 & {v1,v2} is linearly-independent ) by A8, A1, Th62; :: thesis: verum